Regulatory mechanisms of CH4 : air volume ratios on metabolic flux partitioning in methane-oxidizing bacteria and their impact on single cell protein biosynthetic efficiency - Zhang, Jianxiong; He, Jiao; Xin, Jiaying; Cui, Tianyu; Xia, Chungu (Frontiers in Microbiology, 2026)
IntroductionC1 gas bioconversion for single-cell protein (SCP) production offers dual environmental benefits by mitigating greenhouse gases and generating protein resources. This study systematically determined optimal methane-to-air ratios (CH4:air, v/v) for enhancing methane-oxidizing bacteria (MOB) growth and SCP yield under three distinct nitrogen assimilation modes: nitrate-driven pMMO expression, ammonium-driven sMMO expression, and nitrogen-fixing sMMO expression.MethodsExperiments were conducted under three nitrogen assimilation regimes: nitrate-fed pMMO expression, ammonium-fed sMMO expression, and nitrogen-fixing sMMO expression systems. By adjusting the volumetric ratio of methane to air, the effects on bacterial growth, biomass accumulation, specific growth rate, and key enzymatic activities were evaluated. Measured parameters included OD600, cell dry weight, specific growth rate (μmax), and nitrogenase activity in the nitrogen-fixing system. Data from repeated measurements were subjected to statistical analysis to clarify the regulatory role of gas ratios on metabolic pathways.ResultsIn the nitrate-fed pMMO expression system, a CH4:air ratio of 1:3 yielded optimal growth, with an OD600 of 1.11, cell dry weight of 0.44 ± 0.023 g/L, and μmax of 0.022 h−1. Similarly, the ammonium-fed sMMO expression system achieved best performance at the same ratio (OD600 1.19, biomass 0.56 ± 0.014 g/L, μmax 0.025 h−1). In contrast, the nitrogen-fixing sMMO expression system performed better at a lower oxygen ratio (CH4:air = 1:2), reaching an OD600 of 0.62, biomass of 0.28 ±0.008 g/L, nitrogenase activity of 1.09 nmol/(min mg protein), and μmax of 0.016 h−1).DiscussionThe results reveal oxygen's critical dual role: higher O2 levels enhance methane oxidation by activating the copper-dependent catalytic site of pMMO but simultaneously and irreversibly damage the oxygen-sensitive nitrogenase ssential for N2 fixation, suppressing its activity. Conversely, lower O2 protects nitrogenase but limits pMMO efficiency. This creates a fundamental metabolic trade-off where the optimal CH4/O2 ratio balances these opposing effects, strategically partitioning cellular energy either toward efficient methane assimilation (favored by higher O2) or toward the ATP-intensive process of nitrogen fixation (requiring lower O2). These identified gas-ratio thresholds provide actionable parameters for designing scaled SCP bioproduction systems, enabling effective coupling of industrial methane mitigation with sustainable protein synthesis through gas-phase engineering.